Mengingat Dan Mendekatkan Kembali Nilai-Nilai Kearifan Lokal (Piil Pesenggiri) Sebagai Dasar Pendidikan Harmoni Pada Masyarakat Suku Lampung - Masitoh Masitoh (Edukasi Lingua Sastra, 2019)
This article presents about the study of remember and bring it back the local genius based on harmony education among Lampung ethnic society. The purpose of the study was to describe the noble values in local genius Lampung ethnic society regarding the activities of harmonious and peaceful life in the midst of multicultural society. The focus of the study was the philosophy of Lampung people, it was Piil Pesenggiri that had some values: Nemui Nyimah, Nengah Nyappur, Sakai Sambaian, and Juluk Adek/Adok. Those values were hold tight, become spirit, source identity self, dignity, the grandeur of life, etic code/moral (what is Good) in life of Lampung etnic society. This study were collected throught any research paper about Piil Pesenggiri. The results showed that Piil Pesenggiri could play a role in developing the awareness of the importance of group life and encourage cooperation to achieve commons goals.